2019
DOI: 10.3390/agronomy10010043
|View full text |Cite
|
Sign up to set email alerts
|

Do Triticum aestivum L. and Triticum spelta L. Hybrids Constitute a Promising Source Material for Quality Breeding ofNew Wheat Varieties?

Abstract: The aim of this two-year study was to determine whether the contents of macronutrients and macro and microelements in wheat grain can be increased by crossbreeding Triticum aestivum and T. spelta. The experimental material comprised the grains of F6 and F7 hybrids and their parental forms. The element content of grain was determined by ICP-SFMS. Hybrid grains had significantly higher ash contents than bread wheat grain (1.90% and 1.93% versus 1.62%). Crude protein content was lowest in bread wheat grain (11.75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 40 publications
(52 reference statements)
3
11
0
Order By: Relevance
“…Analysis of 5Вq and 5Dq revealed that 5Вq is a pseudogene which codes the complete protein, but takes part in regulation of expression of 5АQ and 5Dq, and combination of 5АQ, 5Вq and 5Dq loci is important for the formation of the ear with free threshing (Konopatskaia et al, 2016). Also, it is possible that in this process a role is also played by regulatory genes which control the expression of dozens of genes, since only single mutation in their sequence could lead to significant changes in phenotype (Suchowilska et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of 5Вq and 5Dq revealed that 5Вq is a pseudogene which codes the complete protein, but takes part in regulation of expression of 5АQ and 5Dq, and combination of 5АQ, 5Вq and 5Dq loci is important for the formation of the ear with free threshing (Konopatskaia et al, 2016). Also, it is possible that in this process a role is also played by regulatory genes which control the expression of dozens of genes, since only single mutation in their sequence could lead to significant changes in phenotype (Suchowilska et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the increasing demand for food products of high quality, the yield continues to be the main determining indicator of profitability of production of grain crops. The recently created highly-productive varieties are often characterized by insufficient quality due to the low content of pro-teins and minerals in the grain (Sharma et al, 2016;Suchowilska et al, 2020). Chasing fast improvement of the genetic potential of yield has led to cultivation of mostly Triticum aestivum L. and T. durum Desf.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on so far published results, the extracts of young spelt grass contain a sufficient amount of key nutrients and biologically active compounds, which can be considered to have beneficial effects on human health. 3 In Montenegro, this is the first study of young spelt grass extract composition.…”
Section: Introductionmentioning
confidence: 99%
“…These efforts gave rise to hybrids between spelt breeding lines and bread wheat cultivars. The relevant research is also being carried out by the Department of Plant Breeding and Seed Production of the University of Warmia and Mazury (UWM) in Olsztyn, Poland [28].…”
Section: Introductionmentioning
confidence: 99%